إسهامات عبد القاهر الجرجاني في نشأة فكرة النظم: The Contributions of ‘Abd al-Qāhir al-Jurjānī to the Emergence of the Concept of al-Naẓm - Bin Md. Noraffendie, Muhammad Nur Afiq Aiman; Bin Nasir, Mohd Shahrizal (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2024)
ملخص البحث يهدف هذا البحث إلى تسليط الضوء على الإسهامات الحقيقية لعبد القاهر الجرجاني في نشأة فكرة النظم التي تعتبر محورا اهتمه الباحثون في مجال اللغة العربية وخاصة علم البلاغة. وكما يسعى هذا البحث إلى استعراض بعض الملامح المهمة التي تكون أفكاره الشخصية. فهذا البحث يعتمد على منهج الوصفي التحليلي، وذلك من خلال جمع المعلومات والدراسات التي تتعلق بشأن فكرة النظم عامة وما حوته عن عبد القاهر الجرجاني التي طرحته الكتب والدراسات السابقة في مختلف الجوانب خاصة، مع إجراء القراءة المتعمقة عليها. وإضافة إلى ذلك، يستخلص هذا البحث بإظهار أبرز إسهاماته الجوهرية بخصوص فكرة النظم التي تميزت عن إسهامات أعلام أخرى في دراستها. وقد أظهرت نتائج هذا البحث، أن عبد القاهر الجرجاني كان من الأعلام البلاغيين الذين أسهموا في توسيع فكرة النظم بوصفها محورا لفهم الحسن البلاغي الذي يكمن في النظم القرآني. وقد أظهر هذا البحث إسهامات عبد القاهر الجرجاني في دمج بين علم النحو والبلاغة في مفهوم النظم الذي جعله إطارا متكاملا لفهم العلاقة بين الألفاظ والمعاني في سياق النصوص ويبرز من هذه العلاقة المعنى الثاني أو السر الكامن. وفي ضوء الإطار النظري والنتائج التي توصل إليها، يوصي البحث على الباحثين إجراء المزيد من الدراسة المعمقة بشأن فكرة النظم إذ لها أهمية في إعانة الناس عامة والمسلمين خاصة إدراك الأسرار البلاغية التي تكمن في الآيات القرآنية. ABSTRACT This research aims to shed light on the significant contributions of ‘Abd al-Qāhir al-Jurjānī to the emergence of the concept of al-Naẓm, which has been a focal point of interest for scholars in the field of Arabic language, particularly in the science of rhetoric. Additionally, the research seeks to highlight some of the key features that define his personal ideas. The research adopts a descriptive-analytical approach by collecting information and studies related to the concept of al-Naẓm in general, and specifically those aspects associated with ‘Abd al-Qāhir al-Jurjānī as presented in various books and previous studies. It also involves in-depth analysis of these resources. Furthermore, this research highlights ‘Abd al-Qāhir al-Jurjānī’s most significant contributions to the concept of al-Naẓm, distinguishing them from the contributions of other prominent figures regarding this issue. The findings of this research reveal that ‘Abd al-Qāhir al-Jurjānī was among the leading scholars of rhetoric who expanded the idea of al-Naẓm, emphasizing it as a core aspect of understanding the rhetorical excellence inherent in the Qur’anic composition. In addition, this research has demonstrated ‘Abd al-Qāhir al-Jurjānī’s contributions to integrating grammar and rhetoric within the concept of al-Naẓm, which he developed into a comprehensive framework for understanding the relationship between words and meanings in textual contexts. This relationship reveals the secondary meaning or hidden essence. Considering the theoretical framework and the findings, the research recommends that scholars undertake further in-depth studies on the concept of al-Naẓm, as it holds significant importance in helping people in general, and Muslims in particular, comprehend the rhetorical secrets embedded in the Qur'anic verses.